2019
DOI: 10.24247/ijmperdaug201944
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of A Compression Ignition Engine Under the Influence of Diesel and Microalgae Biodiesel Blends

Abstract: In the days to come Algae is going to be everything. Wonders would be created using algae. Scientists predict that, from the oxygen that we inhale to the electricity that we use, algae would be the source of energy in the future. were prepared and nominated as MME10D90, MME20D80 and MME30D70. Experiment was conducted on single cylinder four stroke diesel engine and the experimental results were revealed that, at full load condition with MME30D70 the BTE and BSFC were improved by 14.09% and 7.69% respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Biodiesel has been one of the desired alternative fuels to replace petrodiesel due to its similar properties and lower emission of pollutants [2]. The main sources for biodiesel production are edible and non-edible oil crops, such as palm oil, soybean, canola, rapeseed and microalgae [3][4][5]. The conversion of edible oil crops into biofuel has created many issues around the ideology of using food as an energy source.…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel has been one of the desired alternative fuels to replace petrodiesel due to its similar properties and lower emission of pollutants [2]. The main sources for biodiesel production are edible and non-edible oil crops, such as palm oil, soybean, canola, rapeseed and microalgae [3][4][5]. The conversion of edible oil crops into biofuel has created many issues around the ideology of using food as an energy source.…”
Section: Introductionmentioning
confidence: 99%
“…This assessment was concluded that, the PBR cultivation system has a significantly lower risk of production and total cost per gallon oil will be lower than ORP and also, they have emphasized that biofuels from microalgae to be an economically viable industry. N. Charyulu T et al [21] have tested a single cylinder direct injection water cooled diesel engine with diesel and microalgae (Chlorella Vulgaries) methyl ester blends and found that, 30% blend produced better performance, emission and combustion results than that of pure diesel. Gokhan Tuccar et al [22] have carried out an experimental investigation on diesel engine using diesel and microalgae biodiesel blends with the volumetric ratio of 5%, 10%, 20% and 50%, their results showed that although the performance parameters such as torque and brake power values are reduced, the emission parameters like CO and NOx were improved using microalgae biodiesel.…”
mentioning
confidence: 99%